106k views
5 votes
Solve by elimination

Solve by elimination-example-1
User Zuzana
by
5.4k points

1 Answer

3 votes

so, we will eliminate one of the variables, by multiplying one of the equations by "some number" that will be the opposite of the one below, say.... let's eliminate the "y", so if we multiply (-7y) * -2, we get +14y, and 14y - 14y = 0, so let's use that.



\bf \begin{array}{llll} -x~~-7y=~14& * -2\implies &~~2x+14y=-28\\ -4x-14y=28&&-4x-14y=~~28\\ \cline{3-3} &&-2x~~~~~~~~=~~0 \end{array} \\\\\\ -2x=0\implies \boxed{x=0} \\\\[-0.35em] ~\dotfill\\\\ \stackrel{\textit{using that \underline{x} in the 1st equation}}{-(0)-7y=14}\implies y=\cfrac{14}{-7}\implies \boxed{y=-2} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill (0, -2)~\hfill

User Sic
by
5.8k points